Video Game Addictive Symptom Level, Use Intensity, and Hedonic Experience: Cross-sectional Questionnaire Study - Bhavneet Walia; Jeeyoon Kim; Ignatius Ijere; Shane Sanders (JMIR Publications, 2022)
BackgroundThe effects of behavioral addiction to video games has received increasing attention in the literature, given increased use intensity among subgroups of video game players. ObjectiveThis study seeks to empirically determine the relationship between intensity of video gaming and hedonic experience of the player. MethodsWe conducted a survey of 835 individuals who regularly play video games to determine the relationship between intensity of use and hedonic experience. We divided the sample into quartiles by self-reported video game addictive symptom level (from the Internet Gaming Disorder Scale) and conducted polynomial regressions separately for each quartile. ResultsWe found that the higher video game addictive symptom level groups experienced a U-shaped (curvilinear) relationship between hedonic experience and intensity of play, whereas groups with lower video game addictive symptom levels exhibited no such relationship. The coefficients for the highest addictive symptom level group (quartile 4) for marginal effects for hours played per week and hours played per week squared were significantly negative (P=.005) and significantly positive (P=.004), respectively. ConclusionsOur results are consistent with sensitization and tolerance theories, which suggest that high-symptom groups experience frustration and disappointment until they achieve excessive dopamine release, at which point their hedonic experience is expected to improve with additional play. Conversely, low-symptom groups experience no such fall-and-rise pattern. This result is consistent with the outcome that members of the latter group play the game for the direct experience, such that their hedonic experience is more directly related to events occurring in the game than to the increasingly elusive pursuit of excessive dopamine release. We also find that high-symptom groups spend substantially more time and money to support video game use and are much more likely to engage in video game use at the expense of other important activities, such as working, sleeping, and eating.